A cura através do movimento: processos terapêuticos entre mulheres através da disciplina do corpo no Hatha Yoga - Oliveira, Marília Thereza Costa (2019)
This work intends to analyze, in an objetive and subjective way, the benefits of Hatha Yoga practice, in its physical layer, and to provide connections between Yoga's physical, philosofical and spiritual approach and what it arises in the practitioners subjectivities, including their emotions. Looking through an anthropological field of search that lasted 8 months, in which the researcher taught Hatha Yoga to a group of women, victims of violence and trauma of any sort, we pursue to understand Yoga tradition as a healing and a body ressignificance tool, furthermore, of reconstruction for a once trespassed body, after its invasion. Drawing Yoga's History path, we seek to locate, in tantric traditions, Hatha Yoga's former principles, solid foundations of our anthropological field of search, which are, the body as a sacred temple and path to transcendence. On the description and field analysis with the volunteers, it is possible to follow the path of the sacred texts inscriptions in the body through their porosity before the symbol, and, with that in mind, to understand the process of the reinvention of body-temple as sacred again, after the experience of violation, through Hatha Yoga as a tool.